Astrocyte Infection Is Required for Retrovirus-Induced Spongiform Neurodegeneration Despite Suppressed Viral Protein Expression - Cardona, Sandra M.; Dunphy, Jaclyn M.; Das, Alvin S.; Lynch, Connor R.; Lynch, William P. (Frontiers in Neuroscience, 2019)
The ability of retroviruses (RVs) to cause neurodegeneration is critically dependent upon two activities of the envelope protein (Env). First, Env facilitates viral genome delivery to CNS target cells through receptor binding and membrane fusion. Second, Env expression within one or more targets indirectly alters the physiology of certain neurons. Although the major Env expressing CNS cell types have been identified for many neurovirulent RVs, it remains unresolved, which targets play a causal role in neuropathogenesis. Moreover, this issue is complicated by the potential for post infection virus suppression. To address these questions we explored herein, whether and how cryptic neurotropism differences between ecotropic and amphotropic murine leukemia viruses (MLVs) impacted neurovirulence. Neurotropism was first explored ex vivo using 1) acute primary glial cell cultures and 2) neural progenitor cell (NPC)- neural stem cell (NSC) neural sphere (NPH) chimeras. These experiments indicated that primary astrocytes and NPCs acutely restrict amphotropic but not ecotropic virus entry. CNS tropism was investigated using NSC transplant-based Cre-vector pseudotyping wherein mTmG transgenic fluorescent protein reporter mice revealed both productive and suppressed infection. Cre-pseudotyping with FrCasE, a prototypic neurovirulent ecotropic virus, identified glia and endothelia, but not neurons, as targets. Almost two-thirds (62%) of mGFP+ cells failed to show Env expression, suggesting widespread virus suppression. To circumvent RV superinfection interference confounds, targets were also identified using ecotropic packaging NSCs These experiments identified known ecotropic targets: microglia, oligodendrocyte progenitor cells (OPCs) and endothelia. Additionally, one third of mGFP+ cells were identified as protoplasmic astrocytes, cells that rarely express virus in vivo. A CNS targeting comparison between isogenic ecotropic (FrCasE) and amphotropic (FrAmE) viruses showed a four-fold higher astrocyte targeting by FrCasE. Since ecotropic Env pseudotyping of amphotropic virus in the CNS dramatically exacerbates neurodegeneration, these results strongly suggest that astrocyte infection is a major disease requirement. Moreover, since viral Env protein expression is largely subdetectable in astrocytes, minimal viral protein expression appears sufficient for affecting neuronal physiology. More broadly, these findings raise the specter that subdetectable astrocyte expression of exogenous or endogenous RVs could play a major role in human and animal neurodegenerative diseases.